AllocateMate (Version 2): An R package for mate allocation - Hamilton, Matthew (WorldFish, 2024)
AllocateMate is a R package (R Core Team 2020) comprised of two primary functions: allocate.mate.ped and allocate.mate.H. These functions allocate parents to mating pairs based on genetic relationships provided by the user in the form a pedigree file (allocate.mate.ped) or a relationship matrix (allocate.mate.H).